Квантово-хімічне розуміння характеристик ІЧ поглинання деяких структурних фрагментів макромолекул лігніну - Токар, Андрій Володимирович; Tokar, Andriy (Oles Honchar Dnipro National University, 2023)
За допомогою ab initio методів квантової хімії проведено детальне теоретичне дослідження олігомерних продуктів, що відтворюють особливості будови типових структурних фрагментів макромолекул лігніну. Структурування окремих ділянок здійснено на основі транс-коніферилового спирту як базового прототипу з його подальшою димеризацією та одержанням трьох пар ізомерних сполук із різними типами зв’язувань. Їх ранжування за рівнем відносної термодинамічної стабільності показало, що найбільш стійкими є форми (- O-4), (-) та (5-5), тоді як структури (-O-4), (-5) та (4-O-5) виявилися дещо менш стабільними. У процесі обґрунтування спектральних характеристик цих систем із розрахунком коливальних частот у гармонічному наближенні значної уваги приділено ефектам внутрішньомолекулярного водневого зв’язування, що виникає за участю просторово ускладнених гідроксильних груп спиртового або фенольного типу, а також аналізу жорстколанцюгової системи пінорезинолу, що містить у своєму складі біциклічний каркасний фрагмент. Результати розрахунків добре узгоджуються з ІЧ спектральними даними, одержаними експериментальним шляхом, та можуть мати принципове значення з точки зору пошуку потенційних сполук-попередників для подальшого структурування цього нерегулярного біополімеру.. Using the ab initio methods of quantum chemistry, a detailed theoretical investigation of oligomeric products, that reproduce some features of the structure for typical fragments of lignin macromolecules have been carried out. The structuring of individual sections has done on the basis of trans-coniferyl alcohol as a prototype with its subsequent dimerization for three pairs of isomeric compounds with different types of linkages. Their ranking according to the level of relative thermodynamic stability showed, that the forms (-O-4), (-) and (5-5) are the most stable, while the structures (-O-4), (-5) and (4-O-5) turned out to be the less stable ones. When substantiating of the spectral characteristics for these systems with the calculation of vibrational frequencies in the harmonic approximation, considerable attention was paid to the intramolecular hydrogen bonding effects, which occur with some participation of spatially complicated hydroxyl groups of the alcohol or phenolic type, as well as the analysis of the rigid chain of pinoresinol system, which contains a bicyclic cage fragment. The results of calculations are in good agreement with the IR spectral data obtained experimentally, and may be of fundamental importance from the point of view about searching of potential precursor compounds for further structuring of this irregular biopolymer. Using the ab initio methods of quantum chemistry, a detailed theoretical investigation of oligomeric products, that reproduce some features of the structure for typical fragments of lignin macromolecules have been carried out. The structuring of individual sections has done on the basis of trans-coniferyl alcohol as a prototype with its subsequent dimerization for three pairs of isomeric compounds with different types of linkages. Their ranking according to the level of relative thermodynamic stability showed, that the forms (-O-4), (-) and (5-5) are the most stable, while the structures (-O-4), (-5) and (4-O-5) turned out to be the less stable ones. When substantiating of the spectral characteristics for these systems with the calculation of vibrational frequencies in the harmonic approximation, considerable attention was paid to the intramolecular hydrogen bonding effects, which occur with some participation of spatially complicated hydroxyl groups of the alcohol or phenolic type, as well as the analysis of the rigid chain of pinoresinol system, which contains a bicyclic cage fragment. The results of calculations are in good agreement with the IR spectral data obtained experimentally, and may be of fundamental importance from the point of view about searching of potential precursor compounds for further structuring of this irregular biopolymer.
Quantum-Chemical Understanding of the IR Absorption Characteristics for Some Structural Fragments of Lignin Macromolecules
Keywords: ab initio розрахунок; ab initio calculation; ІЧ спектр поглинання; IR absorption spectrum; гармонічна коливальна частота; harmonic vibrational frequency; відносна термодинамічна стабільність; relative thermodynamic stability; структура лігніну; lignin structure